Relationship between labour productivity and design characteristics in high-rise buildings / Ha Duy Khanh, Young Dai Lee and Soo Yong Kim - Ha, Duy Khanh; Lee, Young Dai; Kim, Soo Yong (Faculty of Architecture, Planning & Surveying and UiTM Press, 2014)
Formwork installation, rebar fabrication/installation, and concrete casting are often repetitive in high-rise building projects. Previous studies have shown that labor productivity is significantly affected by many reasons. This study aims to consider the relationship between average labor productivity and design characteristics in typical floors of high-rise building projects. Data were collected through questionnaire which was distributed to experts and experienced people in construction projects. A neural network model was developed to estimate labor productivity. The main result is the comparison between predicted and actual labor productivity for typical floors. The Mean Absolute Percentage Errors (MAPE) are less than 3.5%, and R-squared indices are greater than 85% for all three activities mentioned above. These results showed that the model developed in this study is very appropriate when predicting labor productivity in high-rise building projects.